Nilai-Nilai Religius Pembentuk Akhlak Mulia dalam Novel Assalamualaikum Beijing Karya Asma Nadia: Kajian Struktural Genetik - Lala Nurmala (Universitas Muhammadiyah Prof. DR. HAMKA, 2016)
The study entitled “Nilai-Nilai Religius Pembentuk Akhlak Mulia dalam Novel Assalamualaikum Beijing Karya Asma Nadia (Kajian Struktural Genetik)” is a desrciptive qualitative study using genetic structural approach. The problems discussed in this research are (1) How is the intrinsic structure of Assalamualaikum Beijing novel by Asma Nadia?, (2) What are the religious values which develop good characters in Assalamualaikum Beijing novel from the point of view of the author. The objective of the research is to describe the intrinsic factors of Assalamualaikum Beijing novel, the religious values developing good characters in Assalamualaikum Beijing novel from the point of view of the author. The findings of the study are expected to be beneficial for the teachers of Bahasa Indonesia and Indonesian literature, students as teenagers, the resercher, and the society. The type of the reseach is qualitative descriptive with content analytical technique, while the reseach approach is genetic structural research emphasizing texts as the study objects. The data of this study are sentences, paragraphs, and discources written in Assalamualaikum Beijing novel. The source of the data of this study is Assalamualaikum Beijing novel by Asma Nadia published by PT Mizan Publika, Jakarta, in 2014. Based on the data analysis, it was found out that the religious values developing good characters in Assalamualaikum Beijing novel by Asma Nadia were the good characters to worship Allah SWT covering piety, sincerity, gratitude, obedience to follow Rasulullah, patience, good attitude towards parents, rights and obligations as husband and wife, attitudes with others, and attitiudes among teenagers. The study revealed 85 values forming good characters with the following details; 15 values of piety, 8 values of sincerity, 12 values of gratitude, 7 values of obedience to Rasulullah, 7 values of patience, 7 values of good attitude towards parents, 10 values of rights and obligations as husband and wife, 9 values of good attitude towards others, 8 values of attitude among teenagers. This study concludes that religious values cannot be separated from the influence of the society, family, friends, and self-willingness . Since the good values taken from Assalamualaikum Beijing novel can be used as the source of material for students’ literature study, the values can be implemented in the learning of literature study in schools, especially High Schools.